Rediscovering Resilience : The First Step on the Path to Sustainability - Vadeanu, Alexandru (My University, 2022)
Humankind finds itself in a predicament unlike any ever experienced. Adversities seem to gather around with eager haste, and although resilience has become a priority in discussing governments, academics, and the public alike, its significance and understanding remain hazy. Hence, the adequate response to facing life’s adversities seems to evade humankind. Resilience emphasizes the need to adapt, withstand an undesired situation that threatens the point of functionality and strive for a positive outcome that will bring us one step closer in achieving sustainability. However, resilience as a solution to complex global problems is heavily criticized. One form of criticism is based on postmodern thinking and the analysis of power structures suggesting that instead of accepting the demand for resilience, we should find new pathways by seeking creativity and transformation through power. Power is understood as a Nietzschean philosophical worldview of self-mastery through which adversity is conquered and new meaning is forged, leading to harmony with life itself. This study investigates the concept of resilience in two contexts: the first in connection to positive psychology and the second regarding the political science field. The study uses textual and conceptual analysis in asking the following questions: What is resilience? What are the philosophical characteristics of resilience? What do the implications of resilience entail at the level of human behavior? The analysis shows a strong correlation between values and resilience, concluding that the optimal way forward in dealing with adversities is discovered by adhering to the concept of resilience in relation to values as a precondition for achieving sustainability. As this is a conceptual thesis, emphasis is put on deductions and what implications the concepts analyzed might have, not on a fixed conclusion grounded in data. Thus, the conclusion is left open to debate.
Keywords: resilience, positive psychology, values, will to power, liberal regimes, philosophy, sustainability, politics, neoliberalism